Comment on "Food insecurity and mental health of women during COVID-19: Evidence from a developing country" by Rahman et al. - Lenka Fiala; Anders Kjelsrud; Essi Kujansuu; Abel Brodeur (Institute for Replication (I4R), 2025)
Rahman et al. (2021) study the correlation between mental health and food insecurity during the COVID-19 pandemic in Bangladesh. They report that food insecurity increases in the sample and that this is associated with increased stress. This result is not reproducible from the author-provided dataset. In fact, the data suggests that higher food insecurity reduces stress. Additionally, we identify undisclosed overlaps of respondents from datasets of related papers, with inconsistencies in sample selection and data collection descriptions. Taken together, we believe these issues undermine the credibility of the paper.
Keywords: B41; C12; I12; I18; J16; O12; 330; Reproduction; Replication; Food Insecurity; Mental Health; COVID-19 Pandemic